Mesra Jaya Enterprise: Gift Castle - The Gift Centre / Marlini Ya'ali ... [et al.] - Ya'ali, Marlini; Mohamed Sopafi, Mohd Syawalullah; Sahar, Noridawati; Amir, Jasni; Zakaria, Norlizaayuzah (2001)
Gift is something special that is given from someone to someone else as a token of remembrance. Gift is given on every occasion such as birthdays, weddings, newborn child, festivals and so on. Nowadays, there are many gift shops established everywhere in Malaysia. However, it is hard to find a one-stop place that offers variety of good quality of gift items along with convenient services related to gifts with an affordable price. Therefore, an idea struck our mind to establish 'Gift Castle- The Gift Center' to provide various of good quality of gift items along with convenient services related to gifts with an affordable price. Mesra Jaya Enterprise target customers are everyone from various walks of life, as Mesra Jaya Enterprise principle of more value for money certainly will attract everyone .